Comparative Effectiveness of Famotidine in Hospitalized COVID-19 Patients. (28th April 2021) - Shoaibi, Azza; Fortin, Stephen Patrick; Weinstein, Rachel; Berlin, Jesse A.; Ryan, Patrick
Abstract : INTRODUCTION: Famotidine has been posited as a potential treatment for coronavirus disease 2019 (COVID-19). We compared the incidence of COVID-19 outcomes (i.e., death and death or intensive services use) among hospitalized famotidine users vs proton pump inhibitors (PPIs) users, hydroxychloroquine users, or famotidine nonusers separately. METHODS: We constructed a retrospective cohort study using data from COVID-19 Premier Hospital electronic health records. The study population was COVID-19 hospitalized patients aged 18 years or older. Famotidine, PPI, and hydroxychloroquine exposure groups were defined as patients dispensed any medication containing 1 of the 3 drugs on the day of admission. The famotidine nonuser group was derived from the same source population with no history of exposure to any drug with famotidine as an active ingredient before or on the day of admission. Time at risk was defined based on the intention-to-treat principle starting 1 day after admission to 30 days after admission. For each study comparison group, we fit a propensity score model through large-scale regularized logistic regression. The outcome was modeled using a survival model. RESULTS: We identified 2, 193 users of PPI, 5, 950 users of the hydroxychloroquine, 1, 816 users of famotidine, and 26, 820 nonfamotidine users. After propensity score stratification, the hazard ratios (HRs) for death were as follows: famotidine vs no famotidine HR 1.03 (0.89–1.18), vs PPIs: HR 1.14 (0.94–1.39), and vs hydroxychloroquine: 1.03 (0.85–1.24). Similar results were observed for the risk of death or intensive services use. DISCUSSION: We found no evidence of a reduced risk of COVID-19 outcomes among hospitalized COVID-19 patients who used famotidine compared with those who did not or compared with PPI or hydroxychloroquine users.